GROWING VOCATIONAL TEACHERS' LOYALTY: THE STRATEGIC ROLE OF SERVANT LEADERSHIP AND WORK MOTIVATION - Suharyanto Suharyanto; Sri Setyaningsih; Soewarto Hardhienata (International Journal of Multidisciplinary Research and Literature, 2026)
Teacher organizational commitment is the cornerstone of successful vocational education in Indonesia, particularly amidst the transformation of Vocational High Schools (SMK) into Centers of Excellence and the high mobility of teaching staff. This study examines the influence of servant leadership and work motivation on the organizational commitment of private vocational school teachers. Using a quantitative, path-analytic approach with 119 teachers from private SMK Schools of Excellence in Bogor Regency, Indonesia, the study found that servant leadership has a positive direct effect on organizational commitment (β = 0.184, p < 0.01) and work motivation (β = 0.423, p < 0.001). In contrast, work motivation exerts the strongest direct influence on organizational commitment (β = 0.272, p < 0.01). Work motivation also significantly mediates the relationship between servant leadership and organizational commitment (β = 0.115, p < 0.05). These findings confirm that strengthening service-oriented leadership and enhancing teachers' intrinsic motivation are key strategies for cultivating vocational teacher loyalty.